2015
DOI: 10.1002/mc.22333
|View full text |Cite
|
Sign up to set email alerts
|

Glabridin inhibits cancer stem cell-like properties of human breast cancer cells: An epigenetic regulation of miR-148a/SMAd2 signaling

Abstract: In breast cancer, the cancer stem cells (CSCs) are thought to be the main cause of metastasis and recurrence. Targeting of CSCs or cancer cells with stem cell-like properties has become a new approach for the treatment of breast cancer. Glabridin (GLA), a phytochemical from the root of Glycyrrhiza glabra, exhibited effective antitumor properties in various human cancer cells. However, the roles of GLA in the regulation of CSC-like properties and the underlying molecular mechanisms remain unclear. Here, we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 31 publications
3
59
0
1
Order By: Relevance
“…Furthermore, SER1755 has Pi-Donor hydrogen bond with the ligand. In mouse xenograft models, this glabridin compound was found to attenuated the tumor growth, mesenchymal characteristics, and cancer stem cells-like properties via demethylation-activated miR-148a [22].…”
Section: Glycyrrhetinic Acidmentioning
confidence: 96%
“…Furthermore, SER1755 has Pi-Donor hydrogen bond with the ligand. In mouse xenograft models, this glabridin compound was found to attenuated the tumor growth, mesenchymal characteristics, and cancer stem cells-like properties via demethylation-activated miR-148a [22].…”
Section: Glycyrrhetinic Acidmentioning
confidence: 96%
“…The glabridin (GLA)/miR-148a/SMAD2 axis serves a critical role in modulating CSC-like properties, such as the formation of mammospheres and colonies. GLA-upregulated miR-148a results in a repression of clone formation, as miR-148a is able to inhibit endogenous TGF-β/SMAD2 signaling in BC cells (49). It was identified that miR-99a directly inhibits the mTOR signaling pathway in breast cancer SP cells, which results in the suppression of tumorigenicity in vivo (35).…”
Section: Mirnas Modulate Clonogenicity and Tumorigenicity Of Bcscsmentioning
confidence: 99%
“…Glabridin(GLA), an isoflavane compound in licorice roots, has attracted extensive attention because of its various biological properties, including the anti-proliferative [16], anti-stem cell-like [17], and anti-cancer activities [18]. The results of a previous research had shown that GLA suppressed angiogenesis through FAK/Rho signaling in human non–small cell lung cancer A549 cells and human breast cancer MDA-MB-231 cells [19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous data also detected that repressed NF-kB/IL-6/STAT-3 signal pathway might be responsible for the inhibition of GLA on the angiogenic ability of human breast cancer MDA-MB-231 cells [21]. Recent studies suggest GLA can upregulate miR-148a, suppress the activation of TGF-β/SMAD2 signaling, and attenuate CSC-like functions in HCC and breast cancer cells [17, 22]. In the following study, we hypothesized that in breast cancer cells, GLA partially inhibited angiogenesis through the Wnt/β-catenin signaling pathway and that miR-148a was involved in this process.…”
Section: Introductionmentioning
confidence: 99%